FAKTOR ORANGTUA YANG BERHUBUNGAN DENGAN STATUS IMUNISASI MEASLES RUBELLA (MR) PADA SISWA DI SD INSAN UTAMA - Yolanda, Yolanda; Risnawati, Risnawati; Hestri, Hestri; Ridha, Ridha (JURNAL KESEHATAN KARTIKA, 2025)
Background: The Measles–Rubella (MR) vaccine is a combination vaccine administered to prevent two infectious diseases—measles and rubella—which are particularly dangerous for children and pregnant women. The coverage of Measles–Rubella (MR) immunization remains below the national target and the increasing number of measles–rubella cases highlights the need to identify parental factors influencing immunization uptake to prevent outbreaks and their impact on children. Objective: To analyze parental factors associated with the Measles–Rubella (MR) immunization status of students at Insan Utama Elementary School. Method: This study used a cross-sectional design, conducted from June 25 to July 25, 2025, with a sample size of 63 people selected using purposive sampling. Knowledge and attitude variables were measured using a questionnaire. Data analysis was performed using univariate and bivariate analysis with the Chi-Square test. Results: Of the 63 respondents, the majority had good knowledge (51 people; 81%) and were supportive of MR immunization (50 people; 79%), but only 32 respondents (51%) had complete MR immunization status, and the Chi-Square test showed no significant relationship between parental factors and MR immunization status (p = 0.367). Conclusion: Parental factors that influence the administration of Measles Rubella (MR) immunization are education, occupation, knowledge, and attitude.